Evaluation Of Cell-Free Supernatant Of Lactic Acid Bacteria, Lactiplantibacillus Plantarum K014 Against Skin Pathogen Bacteria - Mlambo, Larry Kurai (2023)
This study aims to evaluate the effects of bioactive metabolites produced by lactic acid bacteria against methicillin-resistant Staphylococcus aureus (MRSA) ATCC43300. A total of six LAB were selected to evaluate the antimicrobial activity against MRSA ATCC43300, a skin pathogen that is highly resistant to most antibiotics.